Replacement of Mouse Microglia With Human Induced Pluripotent Stem Cell (hiPSC)-Derived Microglia in Mouse Organotypic Slice Cultures - Ogaki, Ari; Ikegaya, Yuji; Koyama, Ryuta (Frontiers in Cellular Neuroscience, 2022)
Microglia, the major immune cells in the brain, are reported to differ in gene expression patterns among species. Therefore, it would be preferable in some cases to use human microglia rather than mouse microglia in microglia-targeted disease research. In the past half a decade, researchers have developed in vivo transplantation methods in which human induced pluripotent stem cell-derived microglia (hiPSC-MG) are transplanted into a living mouse brain. However, in vivo transplantation methods are not necessarily accessible to all researchers due to the difficulty of obtaining the materials needed and the transplantation technique itself. In addition, for in vivo systems for microglia-targeted drug screening, it is difficult to control the pharmacokinetics, especially blood-brain barrier permeability. Therefore, in addition to existing in vivo transplantation systems, the development of an ex vivo transplantation system would help to further evaluate the properties of hiPSC-MG. In this study, we aimed to establish a method to efficiently transplant hiPSC-MG into cultured mouse hippocampal slices. We found that approximately 80% of the total microglia in a cultured slice were replaced by hiPSC-derived microglia when innate microglia were pharmacologically removed prior to transplantation. Furthermore, when neuronal death was induced by applying Kainic acid (KA) to slice cultures, transplanted hiPSC-MG changed their morphology and phagocytosed cell debris. Thus, this study provides a method to transplant hiPSC-MG into the mouse hippocampal slice cultures with a high replacement rate. Because the transplanted microglia survived and exerted phagocytic functions, this method will be useful for evaluating the properties of hiPSC-MG ex vivo.